2022
DOI: 10.1111/jan.15341
|View full text |Cite
|
Sign up to set email alerts
|

Structural violence: An evolutionary concept analysis

Abstract: Aims: To enhance conceptual clarity and interdisciplinary understanding of structural violence, and to illuminate its implications for contemporary social justice and health equity research, by: (1) synthesizing scholarly literature pertaining to structural violence and health; (2) defining its key attributes, antecedents, consequences and characteristics; (3) contextually situating this phenomenon over time and across disciplines.Design: A comprehensive review of scholarly health literature pertaining to 'str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…A review of public health research on structural violence found that the literature links outcome categories such as health inequity, injustice, indignity and social disorganisation to structural predictor categories such as social, cultural, economic and political systems (Jackson and Sadler, 2022). Social determinants of health (SDH) – which Jackson and colleagues call a ‘surrogate’ for structural violence – can include housing insecurity, energy insecurity and food insecurity.…”
Section: Structural Violence and Thermal Insecuritymentioning
confidence: 99%
“…A review of public health research on structural violence found that the literature links outcome categories such as health inequity, injustice, indignity and social disorganisation to structural predictor categories such as social, cultural, economic and political systems (Jackson and Sadler, 2022). Social determinants of health (SDH) – which Jackson and colleagues call a ‘surrogate’ for structural violence – can include housing insecurity, energy insecurity and food insecurity.…”
Section: Structural Violence and Thermal Insecuritymentioning
confidence: 99%
“…However, a central challenge still exists regarding theorization, as well as the measurement of SV and its impact on IPV, as well as health outcomes. In a recent paper on the evolutionary concept analysis of structural violence, Jackson and Saddler point out that the lack of conceptual clarity and operationalization of SV prevents the identification of measurable constructs of SV [27]. Moreover, they indicated the need for awareness of the concept of SV and its interdisciplinary usage that could validate and help hypothesis-building in relation to health and well-being [27].…”
Section: Opportunities and Challenges Of Including Structural Violenc...mentioning
confidence: 99%
“…Makwana's research raises the experience of people in India who have limited access to improve their standard of living. Other studies have linked the marginalization and marginalization of vulnerable groups as part of structural violence (Jackson & Sadler, 2022). The marginalization and persecution of disadvantaged groups are also linked to cultural violence.…”
Section: Introductionmentioning
confidence: 99%